19-fs pulse generated by supercontinuum compression - 张华强 王鹏 刘文军 姚翳蕾 徐志敬 李健 (Chinese physics B, 2016)
Supercontinuum generation and compression in a length of 50-ram photonic crystal fiber with pulse of nanojoule energy are investigated theoretically and experimentally. Chirped mirror pair is used for dispersion compensation and pulse compression. Pulse characteristics are measured by frequency-resolved optical gating. And 19-fs pulse is generated.